2015
DOI: 10.1016/j.jacc.2015.05.057
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Follow-Up Left Ventricular Ejection Fraction Associated With Outcomes in Primary Prevention Implantable Cardioverter-Defibrillator and Cardiac Resynchronization Therapy Device Recipients

Abstract: BACKGROUND Heart failure patients with primary prevention implantable cardioverter-defibrillators (ICD) may experience an improvement in left ventricular ejection fraction (LVEF) over time. However, it is unclear how LVEF improvement affects subsequent risk for mortality and sudden cardiac death (SCD). OBJECTIVES We sought to assess changes in LVEF after ICD implantation and the implication of these changes on subsequent mortality and ICD shocks. METHODS We conducted a prospective cohort study of 538 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
81
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 18 publications
9
81
2
1
Order By: Relevance
“…Cumulative evidence suggests that improved LVEF is associated with a decreased risk of mortality and appropriate ICD shock for ventricular tachyarrhythmia, particularly in those whose follow-up LVEF improved to >35%. 26 Consistent with previous findings, our study reported a trend toward an inverse association between LVEF changes and the risk of appropriate shock. These findings underscore that even partial functional improvement in LVEF may reduce subsequent arrhythmic risk while the majority of appropriate ICD firings occur in those in whom LVEF is static or declining despite aggressive HF therapy.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Cumulative evidence suggests that improved LVEF is associated with a decreased risk of mortality and appropriate ICD shock for ventricular tachyarrhythmia, particularly in those whose follow-up LVEF improved to >35%. 26 Consistent with previous findings, our study reported a trend toward an inverse association between LVEF changes and the risk of appropriate shock. These findings underscore that even partial functional improvement in LVEF may reduce subsequent arrhythmic risk while the majority of appropriate ICD firings occur in those in whom LVEF is static or declining despite aggressive HF therapy.…”
Section: Discussionsupporting
confidence: 91%
“…20–24 Among primary prevention ICD patients, 25%–40% improve their LVEF after ICD implantation. 26 Despite the high prevalence of LVEF improvement, little is known regarding the determinants of LVEF changes among primary prevention ICD recipients. In a case-control study of 102 dilated cardiomyopathy patients, shorter QRS duration, female sex, non-ischemic etiology, absence of diabetes, and higher blood pressure were associated with improved LVEF to normal or near-normal with medical therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to findings in this study, Zhang et al have reported improvement in EF to >35% in 25% of primary prevention ICD recipients with a reduced incidence of ICD therapies in patients with EF improvement. 21 Kini et al 22 also reported a lower incidence of ICD therapy after ICD replacement in patients with improvement in EF to >40% (2.8% versus 10.7% per person-year). In contrast to these observations, LVEF improvement during follow-up was not predictive of reduced appropriate ICD therapy in primary prevention recipients in the Defibrillators in Non-Ischemic Cardiomyopathy Treatment Evaluation trial (DEFINITE) and in a cohort of ICD replacement patients.…”
Section: Discussionmentioning
confidence: 97%
“…In this issue of the Journal, Zhang et al(16) step into this maelstrom to offer an important contribution to arrhythmic risk assessment in the HF population. The authors evaluated the association between changes in LVEF after primary prevention ICD and biventricular-pacemaker ICD on ICD shocks and mortality.…”
mentioning
confidence: 99%